Incidence of Uterine Torsion and Related Factors in Buffaloes of Amul Milk Shed Area - Patelvya, Chintan S; Patel, JA; Dhami, AJ; Patel, SB; Makwana, HK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was carried out to find out the retrospective incidence of uterine torsion in buffaloes among obstetrical cases in Amul milk shed area and factors influencing it. Data on 1,13,772 obstetrical cases attended from January 2017 to June 2018 by Amul Veterinarians were collected. Moreover, 50 buffaloes suffering from uterine torsion were taken up during July-December, 2018 to know the side, site, degree of uterine torsion, parity as well as sex and viability of the calf and the dam after detorsion/Caesarean section in the same area. In the retrospective study, a total of 2000 cases of uterine torsion were recorded among total 1,13,772 bovine obstetrical cases, which encompassed 1.76%. Of the 2000 cases, 92.20 (1844) percent torsions were found in buffaloes only. Among 57,111 obstetrical cases attended in buffaloes, the incidence of uterine torsion was 3.23%. Moreover, the region/center-wise incidence of torsion cases varied from 1.30–19.36%. The highest incidence of uterine torsion was found in Anand region (19.36 %) followed by Kathlal (11.23 %) and Mahemdabad (10.14 %) regions, while the lowest incidence was in Virpur (2.06%), Petlad (1.46%) and Piplata (1.30%). It was concluded that buffaloes mostly experience right side (100%), post-cervical (82%) uterine torsion of 270–360° (66%), at full term of gestation (70%) with lower survivability of the calves (30%), however, the survival rate of the dams post-treatment was 90%